2012
DOI: 10.1016/j.ijpsycho.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and psychological responses to laboratory stressors in women: Assessing the roles of menstrual cycle phase, premenstrual symptomatology, and sleep characteristics

Abstract: This study assessed whether premenstrual symptomatology and/or sleep characteristics explain increased luteal phase psychophysiological reactivity to laboratory stressors. We hypothesized that: (1) premenstrual symptoms and sleep characteristics would explain greater luteal versus follicular phase psychophysiological reactivity, (2) symptoms and sleep characteristics would differentially predict psychophysiological reactivity within each cycle phase, and (3) symptoms and sleep characteristics would interact to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Women with neuroticism-related personality traits (Gingnell et al, 2010) and those with altered perception of life events who tend to overinterpret negative life events (Gonda et al, 2010) were shown to have greater sensitivity to stress. Stress was sometimes intentionally induced under laboratory settings through various methods, including cold stimuli, tourniquet ischemic tasks, and tasks to evoke cognitive stress to generate objective stressors and compare different perceptions and reactions among women through various physiological responses (Girdler et al, 2001;Klatzkin et al, 2006;Lustyk et al, 2012).…”
Section: Types Of Stressmentioning
confidence: 99%
See 4 more Smart Citations
“…Women with neuroticism-related personality traits (Gingnell et al, 2010) and those with altered perception of life events who tend to overinterpret negative life events (Gonda et al, 2010) were shown to have greater sensitivity to stress. Stress was sometimes intentionally induced under laboratory settings through various methods, including cold stimuli, tourniquet ischemic tasks, and tasks to evoke cognitive stress to generate objective stressors and compare different perceptions and reactions among women through various physiological responses (Girdler et al, 2001;Klatzkin et al, 2006;Lustyk et al, 2012).…”
Section: Types Of Stressmentioning
confidence: 99%
“…The SPAF is Downloaded by [University of Otago] at 03:44 03 July 2015 a 10-item measure that asks about physical and emotional symptoms related to affect, water retention, and pain (Lustyk et al, 2007;Masho, Adera, & South-Paul, 2005). This is a shortened version of the 95-item Premenstrual Assessment Form; its psychometric properties have been well tested, and it is more effective in assessing changes than other symptom checklists (Lustyk et al, 2007(Lustyk et al, , 2012Masho et al, 2005). The Prospective Record of the Impact and Severity of Menstrual Symptoms (PRISM) was used in three studies (Girdler et al, 2001;Gonda et al, 2010;Klatzkin et al, 2006).…”
Section: Measures Of Premenstrual Symptomsmentioning
confidence: 99%
See 3 more Smart Citations